Pelatihan English Conversation Bagi Guru dan Siswa - Siti Maria Ulfa; Moh. Arief Wahyudi (Universitas Bengkulu, 2023)
This activity is carried out with the aim of conveying information about how English conversation must be carried out by both teachers and students in order to achieve the desired goals, namely being able to communicate well and effectively. The participants in this activity were three English teachers and twelfth grade students totaling thirty seven students and took place in the school’s classroom. The method used starts from introduction, delivery of theory, discussion, implementation of trials, reflection and evaluation. Each stage was well executed and as a result, this activity had a tremendous effect on teachers and students. Teachers can find strategies that they had not previously thought of in teaching speaking skills to students and they feel comfortable when they are taught by adjusting the topics of discussion that are appropriate to their domain. Therefore, it is necessary to carry out activities that are continuous and sustainable so that what is the main goal of students to be able to master English conversation for the world career and a better opportunity to study can be achieved.